A study of the adjunctive therapeutic effects of a 3-week bamboo forest therapy on chronic diseases in the elderly - He, Jing; Wan, Rong; Xiao, Xue; Zhang, Jie; Liang, Yi; Zhu, Zixin; Cao, Yu (Frontiers in Environmental Health, 2025)
IntroductionThe health benefits of bamboo forest recreation on the human body are becoming increasingly recognized. However, limited research has focused on integrating environmental factor monitoring with smart platforms for population health management and assessment.MethodThis study monitors environmental parameters, including anion concentration, temperature, relative humidity, wind speed, acoustic environment, and volatile organic compounds in a bamboo forest, while recruiting elderly participants with essential hypertension, type II diabetes, and sleep disorders. A non-invasive wearable device was employed to track the health of the participants, followed by a 21-day precision health management intervention within the bamboo forest.ResultsThe concentration of negative oxygen ions in this region exceeds 10,000 ions per cm3, alongside terpenes and other health-promoting volatile substances. A total of 70 participants participated in the platform. Compared to baseline measurements, hypertensive participants experienced significant reductions in systolic and diastolic blood pressure, as well as pulse rate (p < 0.001). Diabetic participants showed significant decreases in fasting and pre-bedtime blood glucose levels (p < 0.001), along with reduced blood glucose fluctuations post-meal. Participants with sleep disorders demonstrated statistically significant improvements in key sleep parameters, including the minimum blood oxygen level at sleep onset, the Oxygen Desaturation Index, wake frequency, percentage of rapid eye movement (REM) sleep, and subjective sleep quality (p < 0.05). The overall sleep quality score also showed significant improvement.ConclusionsThis study substantiates the therapeutic potential of bamboo forests in alleviating chronic diseases among the elderly, offering valuable insights for planning “bamboo bath” experiences.